Enhancing Students' Interpersonal Competence Through Outdoor Learning Space-Based Learning: A Case Study at SMAIT Balikpapan, Indonesia - Indar Sri Wahyuni; Bambang Sudarsono; Enung Hasanah (Journal of Science and Education (JSE), 2026)
Interpersonal competence is an essential skill that should be developed among students to prepare them for social life and future professional challenges. However, classroom instruction remains predominantly teacher-centered, providing limited opportunities for students to develop communication, collaboration, empathy, and conflict-resolution skills. This study aimed to describe the implementation of Outdoor Learning Space (OLS) in enhancing students' interpersonal competence at SMAIT Istiqamah Balikpapan Selatan. A qualitative approach with a case study design was employed. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving the principal, vice principal for curriculum affairs, head of the asset department, teachers, the Outdoor Character Building (OCB) coordinator, and students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, and conclusion drawing and verification. Trustworthiness was ensured through source and methodological triangulation. The findings revealed that OLS enhanced students' interpersonal competence through four interconnected components: experiential learning, collaborative discussion and group work, Outdoor Character Building (OCB) activities, and teachers' roles as facilitators. These components created authentic learning experiences that fostered communication, collaboration, empathy, leadership, and constructive conflict-resolution skills. The study concludes that OLS functions not merely as an outdoor learning environment but as a holistic learning ecosystem that simultaneously promotes academic achievement and students' interpersonal competence.